Ultrafast charge dynamics in mesoporous materials used in dye-sensitized solar cells - Tiwana, P (2013)
This thesis is concerned with measuring ultrafast electron dynamics taking place in dye-sensitized mesoporous semiconductor films employed as working electrodes in dye-sensitized solar cells (DSCs). An understanding of these ultrafast charge transfer mechanisms is essential for designing efficient photovoltaic (PV) devices with high photon-to-current conversion efficiency. Optical-pump terahertz-probe (OPTP) spectroscopy is a sub-picosecond resolution, non-contact, photoconductivity measurement technique which can be used to directly measure charge carrier dynamics within nanostructured materials without the need for invoking complex modelling schemes. A combination of OPTP and photovoltaic measurements on mesoporous TiO2 films show an early-time intra-particle electron mobility of 0.1 cm2/(Vs). This value is an order of magnitude lower than that measured in bulk TiO2 and can be partly explained by the restricted electron movement because of geometrical constraints and increased trap sites in the nanostructured material. In addition, the mesoporous film behaves like a nanostructured composite material, with the TiO2 nanoparticles embedded in a low dielectric medium (air or vacuum), leading to lower apparent electron mobility. THz mobility measured in similar mesoporous ZnO and SnO2 films sensitized with the same dye is calculated to be 0.17 cm2/(Vs) for ZnO and 1.01 cm2/(Vs) for SnO2. Possible reasons for the deviation from mobilities reported in literature for the respective bulk materials have been discussed. The conclusion of this study is that while electron mobility values for nanoporous TiO2 films are approaching theoretical maximum values, both intra- and inter-particle electron mobility in mesoporous ZnO and SnO2 films offer considerable scope for improvement. OPTP has also been used to measure electron injection rates in dye-sensitized TiO2, ZnO and SnO2 nanostructured films. They are seen to proceed in the order TiO2 >SnO2 >ZnO. While the process is complete within a few picoseconds in TiO2/Z907, it is seen to extend beyond a nanosecond in case of ZnO. These measurements correlate well with injection efficiencies determined from DSCs fabricated from identical mesoporous films, suggesting that the slow injection components limit the overall solar cell photocurrent. The reasons for this observed difference in charge injection rates have been explored within. It is now fairly common practice in the photovoltaic community to apply a coating of a wide band-gap material over the metal-oxide nanoparticles in DSCs to improve device performance. However, the underlying reasons for the improvement are not fully understood. With this motivation, OPTP spectroscopy has been used to study how the conformal coating affects early-time mechanisms, such as electron injection, trapping or diffusion length. The electron injection process is unaffected in case of TiCl4-treated TiO2 and MgO-treated ZnO, while it becomes much slower in case of MgO-treated SnO2. Finally, a light-soaking effect observed in SnO2-based solid-state DSCs has been examined in detail using THz spectroscopy and transient PV measurement techniques. It is concluded that continued exposure to light results in a rearrangement of charged species at the metal-oxide surface. This leads to an increase in the density of acceptor states or a lowering of the SnO2 conduction band edge with respect to the dye excited state energy level, ultimately leading to faster electron transport and higher device photocurrents.